The life of Saint Pankratios of Taormina : Greek text, English translation, and commentary - Stallman-Pacitti, Cynthia Jean (Byzantina Australiensia, 2018)
The Life of St Pankratios of Taormina describes the mission and martyrdom of St Pankratios, a disciple of the Apostle Peter sent to evangelize Taormina as its first bishop, and purports to have been written by St Pankratios' successor, Euagrios. The text was composed in the early eighth century and is of Sicilian provenance. The Life contributes to our understanding of the Byzantine attitude to the past and of the novelistic approach to hagiography. It touches on the topography of Sicily and Calabria, ecclesiastical arrangements in Sicily, civil and military administration, the Sicilian language question, church decoration, liturgical rites, book production, and the attitude to religious images.